Clicking together Alkynes and Tetracyanoethylene - Nielsen, Mogens Brøndsted (Chemphyschem, 2023)
The [2+2] cycloaddition – retro‐electrocyclization (CA‐RE) reaction allows ready synthesis of redox‐active donor‐acceptor chromophores from an electron‐rich alkyne and electron‐poor olefins like tetracyanoethylene (TCNE). The detailed mechanism of the reaction has been subject of both computational and experimental studies. While several studies point towards a stepwise mechanism via a zwitterionic intermediate for the first step, the cycloaddition, the reaction follows neither simple second‐order nor first‐order kinetics. Recent studies have shown that the kinetics can be understood if an autocatalytic step is introduced in the mechanism, in which complex formation with the donor‐substituted tetracyanobutadiene (TCBD) product possibly facilitates nucleophilic attack of the alkyne onto TCNE, generating the zwitterionic intermediate of the CA step. This Concept highlights the convenient use of the “click‐like” CA‐RE reaction to obtain elaborate donor‐acceptor chromophores and the recent mechanistic results. Click! The [2+2] cycloaddition – retro‐electrocyclization (CA‐RE) reaction is a “click‐like” reaction by which donor‐acceptor chromophores are readily prepared. Mechanistically, it seems to proceed via a stepwise CA step that is promoted by the product itself (autocatalysis), at least in one specific case. This Concept describes some of these recent mechanistic advances.